Makna Simbolik Tradisi Pembacaan Yāsīn Faḍīlah: Studi Living Qur’an di Desa Jono Kecamatan Tawangharjo Kabupaten Grobogan - Ahtim Miladya Rohmah; Anwar Mujahidin (Institut Agama Islam Negeri (IAIN) Keiri, 2022)
This study analyzes the phenomenon of the tradition of reading Yāsīn Faḍīlah in Jono Village, Tawangharjo District, Grobogan Regency, which is unique in its procession, namely that there is a slametan event which is permissible by request according to what ṣāḥibul ḥajat wants. The purpose of this study is to find out the forms of tradition, describe the preservation of tradition, and how symbolic meaning is created in the reading tradition of Yāsīn Faḍīlah. The method used is qualitative with the type of case study research. As for data collection in this study using the method of observation, interviews, and documentation. Meanwhile, for data analysis, Bronislaw Malinowski's functionalism theory and Herbert Blumer's symbolic interactionism theory were used. The results of this study indicate that the tradition of reading Yāsīn Faḍīlah in Jono Village is divided into 3, namely: Pre-Event, Implementation, and Post-Event. The preservation of this tradition is maintained because the forms of these traditions meet the needs of the people in accordance with Malinowski's theory, namely by fulfilling psycho-biological, social structural, and symbolic needs. While the symbolic meaning is created into four parts, including: 1) The symbol of the relationship with God. 2) Symbol of relationship with ancestors. 3) Symbol of relationship with others. 4) Symbol of relationship with oneself.